A MODERATION INSTITUTIONAL OWNERSHIP IMPACT ON FRAUDULENT FINANCIAL REPORTING: FRAUD PENTAGON THEORY PERSPECTIVE - Yusuf, Fatkhur Avi; Rochayatun, Sulis; Kartikasari, Nungki (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2025)
This study aims to evaluate the effect of the elements in the Fraud Pentagon theory, namely pressure, opportunity, rationalization, capability, and arrogance, on fraudulent financial reporting. This research method uses the F-score model to identify potential fraud in financial statements. The research data were obtained from the annual reports of companies engaged in the financial sector and listed on the Indonesia Stock Exchange (IDX) in the 2019-2023 period. By using a purposive sampling technique, 104 samples were obtained. Data analysis was carried out using the panel data analysis method through Eviews software version 12. The results of the analysis show that pressure has a significant effect on fraudulent financial reporting. However, the opportunity, rationalization, capability, and arrogance variables do not show a significant effect. In addition, institutional ownership is not proven to moderate the relationship between the elements of the Fraud Pentagon and fraudulent financial reporting. This study reveals that financial sector companies listed on the IDX tend to face the risk of fraud in financial reporting when under pressure to manipulate. limitations in this study, limited in its population, which only focuses on financial sector companies in Indonesia.